FirstRand : finding its path into the Indian market (B) - Draper, Peter, 1966-; Maunder, Peta Krost (London : Wits Business School, 2016)
In February 2008, eight months after FirstRand Limited sent Stephan Claassen to India to gather insights for a market-entry strategy into that country - the initial preference being to set up as a retail bank - Claassen presented a strategy to the board that focused on setting up as a corporate investment bank in the Africa-India corridor. He knew he had done well in convincing FirstRand's board of the strategy, but now wondered about other opportunities that would present themselves, and how the team in India would incorporate them into what would become FirstRand Bank India.
Originally published in Draper, P., & Maunder, P. K. (2016). FirstRand: Finding its path into the Indian Market (B). WBC-2016-10. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Claassen, Stephan -- Case studies; FirstRand Limited -- Case studies; Banks and banking -- India -- Case studies